2015
DOI: 10.1111/aji.12453
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pregnancy Loss in Women with Killer Cell Immunoglobulin-Like Receptor KIR2DS1 is Associated with an Increased HLA-C2 Allelic Frequency

Abstract: Our results indicate that among KIR2DS1 pos women, the co-expression of HLA-C2 is associated with RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…Our focus on KIR2D(L1/S1) stems from research showing the importance of these two receptors in controlling aspects of placental development and in their association with poor pregnancy outcomes. 9,10,28 Notably, HLA-C2 directed activation of KIR2DS1 41 and the resulting expression of GM-CSF in KIR2DS1 + uNK promotes trophoblast invasion. 28 Moreover, a KIR2DS1containing genotype (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our focus on KIR2D(L1/S1) stems from research showing the importance of these two receptors in controlling aspects of placental development and in their association with poor pregnancy outcomes. 9,10,28 Notably, HLA-C2 directed activation of KIR2DS1 41 and the resulting expression of GM-CSF in KIR2DS1 + uNK promotes trophoblast invasion. 28 Moreover, a KIR2DS1containing genotype (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate (not enough) or inappropriate (too much) uNK activation may contribute to preterm birth, recurrent miscarriage and pre-eclampsia by limiting angiogenesis/artery remodeling or oversensitizing uNK to being cytotoxic. [9][10][11][12] Obesity, with a prevalence between 13% and 18% in women of reproductive age, 13 correlates with higher incidences of poor pregnancy outcomes. 14 For example, pre-existing obesity associates with recurrent miscarriage, 15 gestational diabetes, 16 preterm birth 17 and pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, population genetic studies have revealed associations between KIRs and KIR ligands, and pregnancy disorders such as recurrent miscarriage and preeclampsia. [12][13][14][15][16] However, difficulties in accessing primary uterine tissue have hampered efforts to understand uterine NK cell KIR repertoire composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, HLA-C was not analysed in this study. Although Dambaeva et al did not confirm the association of RM with increased KIR AA genotype or decreased KIR2DS1 frequency, they did find increased C2 + HLA-C partners among the RM cases with KIR AA genotype (Dambaeva et al 2016 ). The scenario that emerges from these three studies suggests that excessive inhibition of uNK cells may be detrimental.…”
Section: Kir and Hla Association With Recurrent Miscarriagementioning
confidence: 97%